Rationale of restaging transurethral resection of bladder tumor in patients with nonmuscle invasive bladder cancer in the current era - Amit Sharma; R. T. Raghavendra; Deepak Biswal; Pradhuman Yadav; Saryu Goel; Satyadeo Sharma (Urology Annals)
Background: We present retrospective data of patients with nonmuscle invasive bladder cancer (NMIBC) who underwent restaging transurethral resection of bladder tumor (Re-TURBT) at a tertiary care center. Materials and Methods: Records of all NMIBC patients undergoing Re-TURBT between March 2021 and September 2023 were retrospectively analyzed. Patients were risk stratified based on TURBT pathology. Re-TURBT was performed between 4 and 6 weeks. Adverse features such as number, size, and appearance were noted. Patients with persistent disease at Re-TURBT were counseled for early cystectomy with urinary diversion or intravesical Bacillus Calmette–Guerin (BCG). In case of disease upstaging, patients were counseled for radical cystectomy. Results: Thirty-eight NMIBC patients (30 males and 8 females) underwent Re-TURBT. Six patients had residual/persistent disease at 6 weeks, all high risk and high grade (HG, P value not significant, P = 0.31). There was no association with number and appearance of tumors with residual/persistence at 6 weeks. The mean lesion size on imaging in cases with and without residual disease was 3.32 ± 0.86 versus 3.39 ± 0.92 cm, respectively, P value not significant (0.868). There was no residual disease in the low-grade (LG) pT1 group, but HG pTa and pT1 (n = 3) had residual disease. Four HG pT1 patients opted for early cystectomy. Two patients each had pT0 and two pT2. At 3 months of follow-up, urethral strictures were seen both in high risk and intermediate risk. Among four patients who had stricture, meatal stenosis was common (50%, n = 2). Two patients had long-segment stricture requiring perineal urethrostomy with stage I Johannsen repair. All HG pT1 lesion patients eventually underwent cystectomy (3 were under staged and two treated completely with TURBT, one with TURBT + BCG and one patient progressed to metastasis). Conclusion: Re-TURBT is essential for the management of HG pTa and HG pT1 lesions for accurate staging and treatment of residual disease. However, LG pT1 patients can safely be excluded from Re-TURBT.